2015
DOI: 10.7314/apjcp.2015.16.14.5703
|View full text |Cite
|
Sign up to set email alerts
|

Anti Proliferative Properties of Melissa officinalis in Different Human Cancer Cells

Abstract: manner, suggesting that an optimal biological dose is more important than a maximally tolerated one. Moreover, the antiprolifreative effect of MO seems to be tumor type specific, as hormone dependant cancers were more sensitive to antitumoral effects of MOE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…8 Some studies have also reported antibacterial, antifungal and antiinflammatory activities, 9 while others have reported antitumoral effects for some Melissa officinalis extracts on some human tumor cell lines. [10][11][12] In order to understand the antitumor activity of this plant, several studies have been conducted to learn more about its composition. M. officinalis is composed of polyphenolic compounds such as caffeic acid derivatives (mostly rosmarinic acid), flavonoids and essential oil.…”
Section: 6mentioning
confidence: 99%
“…8 Some studies have also reported antibacterial, antifungal and antiinflammatory activities, 9 while others have reported antitumoral effects for some Melissa officinalis extracts on some human tumor cell lines. [10][11][12] In order to understand the antitumor activity of this plant, several studies have been conducted to learn more about its composition. M. officinalis is composed of polyphenolic compounds such as caffeic acid derivatives (mostly rosmarinic acid), flavonoids and essential oil.…”
Section: 6mentioning
confidence: 99%
“…Our results confirm the cytotoxic activity previously reported for lemon balm ethanolic extracts on cancer cells but indicate significant antiproliferative activity at much smaller doses than previously used, in the form of ethanolic extracts. Additionally, we compared the effects on the two different types of breast cancer cells, observing a slightly more significant reduction in cell viability exerted on the estrogen receptor positive MCF-7 cells, as previously reported [7].…”
Section: Cell Viability Effect Against Mcf-10a Breast Epithelialmentioning
confidence: 71%
“…e source of natural compounds investigated here is Melissa officinalis L. (MO), a perennial aromatic plant belonging to the Lamiaceae family, also called lemon balm due to its lemon scent. e chemical composition consists in low amounts of essential oils, triterpenes, and important concentrations of polyphenols (caffeic acid derivatives as rosmarinic acid and flavonoids) [7,8]. Although distributed worldwide, the plant commonly grows in the Mediterranean region and Western Asia, being intensively cultivated in Europe [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous specific biochemical activities have been reported 17 such as acetylcholinesterase inhibition and antioxidant activity 18 and its use for the treatment of cancer 19,20 and of diabetes 21 have been evaluated.…”
Section: Introductionmentioning
confidence: 99%